The Content of Imagined Sounds Changes Visual Motion Perception in the Cross-Bounce Illusion - Berger, Christopher C. (Sci Rep, 2017)
Can what we imagine hearing change what we see? Whether imagined sensory stimuli are integrated with external sensory stimuli to shape our perception of the world has only recently begun to come under scrutiny. Here, we made use of the cross-bounce illusion in which an auditory stimulus presented at the moment two passing objects meet promotes the perception that the objects bounce off rather than cross by one another to examine whether the content of imagined sound changes visual motion perception in a manner that is consistent with multisensory integration. The results from this study revealed that auditory imagery of a sound with acoustic properties typical of a collision (i.e., damped sound) promoted the bounce-percept, but auditory imagery of the same sound played backwards (i.e., ramped sound) did not. Moreover, the vividness of the participants’ auditory imagery predicted the strength of this imagery-induced illusion. In a separate experiment, we ruled out the possibility that changes in attention (i.e., sensitivity index d′) or response bias (response bias index c) were sufficient to explain this effect. Together, these findings suggest that this imagery-induced multisensory illusion reflects the successful integration of real and imagined cross-modal sensory stimuli, and more generally, that what we imagine hearing can change what we see.